The Impact of Artificial Intelligence Technology Integration on the Indonesian Language Learning Process in Higher Education - Muh. Safar (Journal of Pedagogi, 2025)
The integration of artificial intelligence (AI) technology into Indonesian language learning in higher education presents both significant opportunities and significant challenges. AI has been shown to improve the quality of learning through automated feedback, linguistic analysis, and personalized recommendations that support students' writing skills, vocabulary mastery, and academic literacy. Lecturers also benefit from reduced technical burdens, allowing them to focus more on the substance of their thinking and the development of critical thinking skills. However, research findings indicate the risk of over-reliance on technology, which can undermine students' creativity, reflection, and originality. Other challenges arise from ethical aspects, such as the potential for conceptual plagiarism and stylistic homogenization. To anticipate these issues, strong digital literacy, ethical awareness, and clear institutional regulations are needed so that AI can be positioned as a pedagogical partner, not a substitute for the intellectual process. This study used a descriptive qualitative approach involving lecturers and students as participants, and analyzed the dynamics of AI use through interviews, observations, and document reviews. The findings emphasize the importance of curriculum reform that integrates digital literacy, ethical use of technology, and critical thinking skills. With adaptive pedagogical strategies, AI can enrich the learning experience without sacrificing the humanistic values of language.